The Influence of Entrepreneurial Orientation, Market Orientation, and Corporate Governance on Firm Performance: The Mediating Role of Innovation Capability - Rani Juniar Hartono; J.E. Sutanto (Green Publisher Indonesia, 2026)
This study is motivated by the increasing demand for manufacturing firms, particularly in the tobacco industry, to enhance competitiveness through innovation, strategic orientation, and effective governance. Despite their significant contribution to economic growth and employment, many family-owned firms still face challenges in maintaining stable performance due to weak innovation capability, limited market responsiveness, and informal governance structures. This study aims to analyze the influence of Entrepreneurial Orientation, Market Orientation, and Corporate Governance on Firm Performance, with Innovation Capability as a mediating variable. The research adopts a quantitative approach using a census sampling technique involving 166 employees of PT Tiga Berlian Anugrah Jaya. Data were analyzed using Structural Equation Modeling (SEM) with SmartPLS 4.0, supported by validity and reliability testing. The results show that Entrepreneurial Orientation, Market Orientation, and Corporate Governance have positive and significant effects on both Innovation Capability and Firm Performance. Furthermore, Innovation Capability partially mediates the relationship between these variables and Firm Performance, indicating its crucial role in translating strategic orientation into performance outcomes. In conclusion, strengthening Innovation Capability, supported by strategic orientation and good governance, is essential for improving Firm Performance and ensuring sustainable competitiveness in family-owned manufacturing companies.